BENTUK PENYAJIAN DAN FUNGSI KESENIAN TUMBUAK BANYAK DI DESA UJUNG PADANG KECAMATAN PANTI KABUPATEN PASAMAN - Neneng Apriani; Marzam Marzam; Esy Maestro (SENDRATASIK UNP, 2012)
The purpose of this research is to know the presentation types and function of Tumbuak Banyak in Ujung Padang village. In this writing, the writer saw the life performance done in Mr. Alan house yard because his daughter Lusi Oktaviani want to get married. There are some elements in Tumbuak Banyak music presentation that is: players, music instrument, costume, place and time performance and audience. While the functions of Tumbuak Banyak music is entertainment, communication device, and sosial integration.